PREDICTING ELECTRIC CAR PURCHASE INTENTIONS AMONG INDONESIA'S MILLENNIALS - Akbar Maulana Firmansyah; Sri Hartini (SEAN Institute, 2022)
Indonesia is a major energy-consuming country and is under pressure to improve its energy efficiency as well as reduce its carbon emissions. Electric cars, as an energy-efficient transport innovation, have the potential to alleviate environmental problems. This study aims to investigate Indonesian millennials' purchase intentions for electric cars by using an extended framework of the theory of planned behavior (TPB). We derived the model through structural equation modeling of a sample of 425 respondents in Indonesia. The findings of this model indicate that consumer attitude, subjective norms, and perceived behavioral control have significant positive influences on the purchase intention of electric cars. Furthermore, our results indicated that environmental concerns have a significant effect on attitude, subjective norm, and purchase intention for electric cars, but not perceived behavioral control. This study contributes to enriching the understanding of the intention to purchase an electric car among millennials in Indonesia.